A ward-based time study of paper and electronic documentation for recording vital sign observations. (11th February 2017) - Wong, David; Bonnici, Timothy; Knight, Julia; Gerry, Stephen; Turton, James; Watkinson, Peter
Abstract: Objective: To investigate time differences in recording observations and an early warning score using traditional paper charts and a novel e-Obs system in clinical practice. Methods: Researchers observed the process of recording observations and early warning scores across 3 wards in 2 university teaching hospitals immediately before and after introduction of the e-Obs system. The process of recording observations included both measurement and documentation of vital signs. Interruptions were timed and subtracted from the measured process duration. Multilevel modeling was used to compensate for potential confounding factors. Results: In all, 577 nurse events were observed (281 paper, 296 e-Obs). The geometric mean time to take a complete set of vital signs was 215 s (95% confidence interval [CI], 177 s–262 s) on paper, and 150 s (95% CI, 130 s–172 s) electronically. The treatment effect ratio was 0.70 (95% CI, 0.57–0.85, P  < .001). The treatment effect ratio in ward 1 was 0.37 (95% CI, 0.26–0.53), in ward 2 was 0.98 (95% CI, 0.70–1.38), and in ward 3 was 0.93 (95% CI, 0.66–1.33). Discussion: Introduction of an e-Obs system was associated with a statistically significant reduction in overall time to measure and document vital signs electronically compared to paper documentation. The reductions in time varied among wards and were of clinical significance on only 1 of 3 wards studied. Conclusion: Our results suggest that introduction of an e-Obs system could lower nursing workload as well as increase documentation quality.